Microscopic surgery for the repair of painful varicocele- efficacy and predictors of successful outcomes - Bercovich, Shayel; Hendel, Hen; Ventura, Yossi; Golan, Shay; Aharony, Shachar; Shoshany, Ohad (Basic and clinical andrology, 2025)
Surgical repair can be offered to patients with scrotal pain of suspected varicocele origin. The estimated success rate of pain resolution is approximately 80%, although recent publications have been inconsistent. Predictive variables for successful outcomes remain contested. The current study aimed to evaluate the efficacy of microscopic repair in resolving varicocele pain and to identify variables that predict successful outcomes. During the study period, microscopic subinguinal varicocelectomy was performed in 59 patients with varicocele-related pain. Grade III left varicocele was present in 36 (61%) patients. The median width of the left varicocele, as measured by ultrasound, was 4.2 mm (IQR 4-5), with reflux identified in 39 (66%) patients. The most common type of pain-dull pain-was present in 39 (66%) patients. Exertional pain and sharp pain were reported by 11 (19%) and 9 (15%) patients, respectively. The median follow-up time was 24 months (IQR 13-35), while 46 (78%) patients were contacted by telephone more than 12 months after surgery. Fifty (85%) patients reported complete pain resolution, while partial resolution and persistent pain were reported by 4 (6%) and 5 (9%) patients, respectively. Two variables that increased the risk of pain persistence were repeat varicocele repair surgery and pain as a secondary or additional indication for surgery. Follow-up time of more than 12 months after surgery reduces the risk of pain persistence. A varicocelectomy is a good option for resolving painful varicocele in most patients, especially those whose only indication for surgery is pain. Repeat varicocele surgery appears to increase the risk of persistent pain. A longer follow-up period (more than 12 months after surgery) increases the chances of pain resolution.